Direct growth and photoluminescence of silicon nanowires without catalyst - Al-Ruqeishi, M.S.; Nor, R.M.; Amin, Y.M.; Al-Azri, K. (Elsevier, 2017)
One-dimensional (1D) silicon nanowires (SiNWs) were fabricated on catalyst free Si (1 0 0) substrate using a thermal evaporation method. Based on SVLS growth mechanism, the obtained SiNWs were 30 to 265 nm in diameter and 1.7 μm to several tens of microns in length. It was found that the presence of graphite powder only is enough to accomplish growth. A systematic study of how the growth conditions, such as the Ar carrier gas flow rate, and the growth time was performed. There are five resultant PL peaks: two blue emission peaks 465 nm (2.67 eV) and 482 nm (2.57 eV) and two green bands centered at 502 nm (2.47 eV) and 526 nm (2.36 eV) and one ultraviolet emission peak at 350 nm (3.54 eV). The theory behind these emissions was discussed.